A novel multi-criteria group decision-making method based on Aczel–Alsina spherical fuzzy aggregation operators: Application to evaluation of solar energy cells. (1st August 2022) - Naeem, Muhammad; Ali, Jawad
Abstract: Keeping in view the significance of spherical fuzzy set (SFS), this research focuses on innovative multi-criteria group decision-making (MCGDM) technique for coping with spherical fuzzy scenarios. To serve this purpose, we explore AczelAlsina spherical fuzzy operational laws and their desirable characteristics. Based on these new operational laws, we expound various aggregation operators, namely Aszel-Alsina spherical fuzzy weighted averaging (AASFWA) operator, AczelAlsina spherical fuzzy ordered weighted averaging (AASFOWA) operator, AczelAlsina spherical fuzzy hybrid averaging (AASFHA) operator, Aczel-Alsina spherical fuzzy weighted geometric (AASFWG) operator, AczelAlsina spherical fuzzy ordered weighted geometric (AASFOWG) operator, and AczelAlsina spherical fuzzy hybrid geometric (AASFHG) operator. Besides, some fundamental results of the newly devised aggregation operators are outlined and verified. In reliance on the propound operators, a step-wise MCGDM method is endowed, and then a case study is given to illustrate the practicality of the presented approach. Additionally, detailed parameter analysis and a systematic comparative study are carried out to verify the stability and validity of the explored works.